ANALYSIS OF THEORETICAL SOURCES OF RESEARCHING WAYS OF FORMING POLITICAL CULTURE AMONG STUDENTS - Artikova Nargiza Akramovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article covers the sociology of youth studied by researchers, their moral and aesthetic views, the practice of youth politics, the issues of positive and negative influence of youth organizations on the development of society, and the content of destructive ideas among young people.